Snail meat consumption in Buea-Cameroon: exposures to foodborne pathogens through social practices assessed in 2019 and 2021 - Mary Nkongho Tanyitiku; Graeme Nicholas; Jon J. Sullivan; Igor C. Njombissie Petcheu; Stephen L. W. On (BMC, 2022)
Abstract Background Snail meat is an important source of nutrition in Cameroon, but the food safety risks are poorly understood. We characterized public health risks from snail meat consumption as a social system in Cameroon, by examining local snail practices that expose snail meat handlers and consumers to foodborne pathogens. Methods We used exploratory qualitative approaches, that is, lived experience, face-to-face in-depth interviews, participant observation and a focus group, to explore fifteen key informants' routines and lived experiences, and perceptions of two health officials on the food safety practices around snail meat consumption in Cameroon. This information was organized and interpreted using Soft Systems Methodology and Social Practice Theory, which permitted a systemic appreciation of local practices. Results We distinguished five kinds of actors (snail vendors, market sellers, street vendors, street eaters and home consumers), who performed seven successive practices (picking, selling, cracking, washing, cooking, hawking and eating). We then identified three worldviews about snails: family support or to reduce poverty, a source of nutrition and a food choice (taste, preference). Our findings revealed participants' competences were based on childhood learning and 'inborn' experiences, and materials used in snail activities reflected participants' parentage and 'state of poverty'. Although most interviewees highlighted 'unhygienic conditions' when explaining snail picking locations, participants believed washing and cooking should kill all contaminants. Conclusion Several opportunities for human exposures to foodborne pathogens including snail picking in domestic wastes and sewage, the selling of unpackaged live snails, improper snail meat washing and hawking in loosely closed buckets, were apparent from our analysis. These findings suggest fruitful opportunities aimed at improving health outcomes among African snail meat handlers and consumers.